A feminilidade e a mulher na obra de Sigmund Freud - Domingues, Mariana Rosa Cavalli (2009)
Studies about woman and about femininity, inside the psychoanalytic field may follow some very different rumors. The theme is enclosed by polemics and contradictions, once the after-Freud authors such as Klein, Brunswick, Bonaparte, Muller, Horney, Jones and Lacan introduce different points of view and disagree, even in the interpretation, with what Freud presented in his works. This survey aims to bring back the Freudian theory about woman and femininity, as well as solve some theoretical conflicts based on the misinterpretation of his texts. For a better understanding of the problem a brief description of the historic track of the theories about woman and femininity in the psychoanalytic stroke was accomplished. Among the said authors, stand out Lacan, for his innovations in the femininity conception and the feminine enjoyment. However, the mean objective of this work is Freud´s theory, that led him up to clinic studies. Hysteria, phobia and obsession are the pathologies found in the woman analised by Freud and that are part of this work. Each one of these diseases show a different logic in the production of symptoms, however all of them contribute to the construction of a theory about the feminine. In the works that talk about social themes antrophology, artistic and literary, Freud define the woman´s place in the social function, as well as he claim his point of view about the subject. References of femininity can be found in seductive and dangerous women as Medusa; and at the same time in feminine figures that represent love and fertility. Freud describe women as defenders of the familiar institution, that sometimes do not consider the social rules. This way of being, typically feminine hasn´t appeared just because of the culture of a civilization but also because of the sexuality. So, Freud´s text about feminine sexuality are also very import sources of woman conception. The castration complex, appeared with the investigation about the anatomic difference between the sexes and caused psychics consequences that brought the self satisfaction. So, the idea that Freud had created a falocentric theory in which the woman is always subordinate to her husband came on the scene. Trying to take part in this critic about the Freudian model, Birman propose a new view about the femininity. The definitions about feminine, though, can lead the psychoanalysis and the psychoanalysis philosophy theorists as David-Ménard to study about the universality of the femininity construction in Freud and Lacan. Thus, the study about femininity and the woman is led to a way across the Freudian work and includes experience in the psychosexual and cultural environment education.